NEGARA DAN BATAS SOSIAL (Studi Kasus: Pengaturan Izin Terhadap Warga Negara Pelaku Kawin Campur di Indonesia) - Arimurti, Ursula; Erawan, I Ketut Putra; Azhar, Muhammad Ali (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
The state has the meaning of a social group that has a certain area in the organization and under an effective political and governmental institution, has political ties, is sovereign, so that it is entitled to its national goals. Politics and bureaucracy are two different institutions but have a close correlation. Legal protection is a right for all citizens in Indonesia contained in Law of the Republic of Indonesia Number 6 of 2011 concerning Immigration. On the other side for foreigners working in Indonesia regulated in Law No. 13 of 2003 concerning Manpower. Immigration policy mentioned above relating to Rights and Obligations to families due to mixed marriages, both of these laws are capable of causing legal uncertainty for foreign nationals, especially foreigners who are intermarried who want to work in Indonesia.